Early-age rheology and hydration control of ternary binders for 3D printing applications. (December 2022) - Das, Arnesh; Reiter, Lex; Mantellato, Sara; Flatt, Robert J.
Abstract: Achieving and controlling the desired strength build-up is important for 3D concrete printing. In this paper, we investigate the possibility of using calcium aluminate cement (CAC) as an accelerator for Ordinary Portland Cement (OPC) for 3D extrusion printing. Both ternary and binary cement systems were studied whereby for the former, the third component was a calcium sulfate source (C$). Experiments are conducted on mixes both in presence and absence of retarders. They focus on hydration progress, evolution of rheological properties and microstructural development. It is concluded that CAC-C$ can be effectively used as an accelerator to achieve the desired rates of strength build-up. Additionally, it is shown that strength build-up has is directly related to CAC dosage, irrespective of the presence of retarders. Based on microstructure characterization results, AFt and AH3 are found to be formed in the first hour after acceleration and responsible for the observed strength build-up.